A Study on Managers' Creation of Budgetary Slack in Emerging Economies: The Case of Vietnam - Quang-Huy Ngo; Thi-Nam-Ninh Doan; Thanh-Nha Huynh (Asian Journal of Accounting Research, 2017)
Although the budgeting literature well documents managers' creation of budgetary slack in developed economies, lack of attention has been paid to this behaviour in emerging economies. It is doubtful that some unique characteristics, only existing in emerging economies, cause this behaviour to be different than the budgeting literature predicts. Since there is no study examining managers' creation of budgetary slack in emerging economies, such as Vietnam, to get insight into whether or not these characteristics cause the differences, the aim of this study is to replicate prior budgeting studies by using Vietnamese samples. Particularly, we investigated the impact of budgetary participation, budget emphasis, information asymmetry, and the interactions between these variables on managers' creation of budgetary slack. Data obtained from the questionnaire sent to 99 Vietnamese managers shows that the last two variables and the interaction between them induce managers' creation of budgetary slack. However, the results also indicate that the first variable and the interaction between this variable and the other two variables respectively have no impact on managers' creation of budgetary slack. These results provide some insight into the creation of budgetary slack of Vietnamese managers for future studies to extend the line of research.